Diallyl Disulfide Attenuates Ionizing Radiation-Induced Migration and Invasion by Suppressing Nrf2 Signaling in Non–small-Cell Lung Cancer. Issue 3 (2nd August 2021) - Xu, Shuai; Huang, Hefa; Tang, Deping; Xing, Mengjie; Zhao, Qiuyue; Li, Jianping; Si, Jing; Gan, Lu; Mao, Aihong; Zhang, Hong
Non–small-cell lung cancer (NSCLC) is the leading cause of cancer-associated deaths. Radiotherapy remains the primary treatment method for NSCLC. Despite great advances in radiotherapy techniques and modalities, recurrence and resistance still limit therapeutic success, even low-dose ionizing radiation (IR) can induce the migration and invasion. Diallyl disulfide (DADS), a bioactive component extracted from garlic, exhibits a wide spectrum of biological activities including antitumor effects. However, the effect of DADS on IR-induced migration and invasion remains unclear. The present study reported that IR significantly promoted the migration and invasion of A549 cells. Pretreatment with 40 μM DADS enhanced the radiosensitivity of A549 cells and attenuated IR-induced migration and invasion. In addition, 40 μM DADS inhibited migration-related protein matrix metalloproteinase-2 and 9 (MMP-2/9) expression and suppressed IR-aggravated EMT by the upregulation of the epithelial marker, E-cadherin, and downregulation of the mesenchymal marker, N-cadherin, in A549 cells. Furthermore, DADS was found to inhibit the activation of Nrf2 signaling. Based on our previous results that knockdown of Nrf2 by siRNA suppressed IR-induced migration and invasion in A549 cells, we speculated that DADS attenuated IR-induced migration and invasion by suppressing the activation of Nrf2 signaling in A549 cells.